Raffinose Family Oligosaccharides Act As Galactose Stores in Seeds and Are Required for Rapid Germination of Arabidopsis in the Dark - Gangl, Roman; Tenhaken, Raimund (Frontiers in Plant Science, 2016)
Raffinose synthase 5 (AtRS5, At5g40390) was characterized from Arabidopsis as a recombinant enzyme. It has a far higher affinity for the substrates galactinol and sucrose than any other raffinose synthase previously reported. In addition raffinose synthase 5 is also working as a galactosylhydrolase, degrading galactinol, and raffinose under certain conditions. Together with raffinose synthase 4, which is predominantly a stachyose synthase, both enzymes contribute to the raffinose family oligosaccharide (RFO) accumulation in seeds. A double knockout in raffinose synthase 4 and raffinose synthase 5 (ΔAtRS4,5) was generated, which is devoid of RFOs in seeds. Unstressed leaves of 4 week old ΔAtRS4,5 plants showed drastically 23.8-fold increased concentrations of galactinol. Unexpectedly, raffinose appeared again in drought stressed ΔAtRS4,5 plants, but not under other abiotic stress conditions. Drought stress leads to novel transcripts of raffinose synthase 6 suggesting that this isoform is a further stress inducible raffinose synthase in Arabidopsis. ΔAtRS4,5 seeds showed a 5 days delayed germination phenotype in darkness and an elevated expression of the transcription factor phytochrome interacting factor 1 (AtPIF1) target gene AtPIF6, being a repressor of germination. This prolonged dormancy is not seen during germination in the light. Exogenous galactose partially promotes germination of ΔAtRS4,5 seeds in the dark suggesting that RFOs act as a galactose store and repress AtPIF6 transcripts.